(untitled) (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Stillbirth is a disastrous event faced by the obstetrician. Each stillbirth is a tragedy having devastating implications for mothers, their families and the health personnel. Globally it remains a significant public health issue, particularly in developing countries like Bangladesh. An understanding of the risk factors associated with stillbirth will facilitate optimum quality of maternal and child health services; which leads to reduce the burden of death. Objective: To determine the factors associated with stillbirth in a tertiary care hospital. Methodology: A descriptive type of cross sectional study was conducted in the department of Obstetrics and Gynecology of Shaheed Suhrawardy Medical College Hospital from 1st January 2019 to 31th December 2019. Total 32 pregnant women who had stillbirth occurred during the study period were included in this study. Non probability purposive sampling technique was followed as per inclusion and exclusion criteria. Result: Total stillbirth reported were 32 (3.37% of total births). Maximum cases were primigravida (65.62%) with illiterate (71.87%), low socio-echonomic status (68.75%) and lack of Ante natal care(56.25%). Main causes of stillbirth were hypertensive disorders(15.6%), labour abnormalities(6.25%), other medical disorders(9.37%), infections(3.12%), Antepartum haemorrhage (12.5%), prematurity (12.5%), cord accidents(3.12%), IUGR(6.25%),birth asphyxia (6.25%) and post maturity(6.25%). Conclusion: Hypertension and other medical disorders, Antepartum haemorrhage, labour abnormalities, prematurity, post maturity, IUGR and birth asphyxia were identified as the highest risks for stillbirth which can be reduced by early recognition of the problem with regular antenatal check-up, colour Doppler ultrasound to diagnose fetal growth restriction and cord abnormalities, anomaly scan, intrapartum use of CTG to know fetal distress and use of partograph to prevent prolongation of second stage of labour and timely obstetric intervention will help in reduction of stillbirth. J Shaheed Suhrawardy Med Coll 2021; 13(1): 15-19